Innovation management in global competition and competitive advantage - Dereli, Deniz Dilara (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 AE Amsterdam, Netherlands, 2015)
Increasing competition due to the liberalization of world trade has led to the production of goods and services according to new needs arising in the global market. Obtaining an advantageous position in the global competitive environment depends on determining right strategies and creating different values. Dynamic market structure, differing market conditions and the existence of innovative competitors make competition even more intense. Nowadays, objectives such as increasing productivity and profitability, gaining new markets and improving existing market shares are reached through innovation activities. Therefore, companies exert themselves to develop innovative skills, gain sustainable abilities and upgrade their performances. In this context, innovation has been one of the essential elements of competitive advantage. New goods and services must be produced in new ways and by adapting the inside and outside applications to the new developed methods, the organizational processes must be restructured. Not only to produce new goods and services, it is also important to manage it as a process. For determination of innovation performance, it is very significant to address all the factors affecting the innovation management process with a holistic approach. While rightly determining needed technology and management stands out as an important element of innovation management, the human and structural adjustment of the organization is also gaining importance in innovation performance. In the global competitive environment, organizational and managerial innovations are the keys to success for companies. While technology and research and development activities significantly influenced the organizational structure and culture, right innovation management provides a competitive advantage. This study aims to evaluate the impact on the competitive advantage of innovation management by putting out the importance of innovation management. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Innovation; Innovation Management; Competition